Comparative performances of serologic and molecular assays for detecting human T lymphotropic virus type 1 and type 2 (HTLV-1 and HTLV-2) in patients infected with human immunodeficiency virus type 1 (HIV-1) - Campos,Karoline Rodrigues (2017)
ABSTRACT The present study evaluated several techniques currently available (commercial kits and in-house assays) for diagnosing human T lymphotropic viruses types 1 and 2 in two groups of patients enrolled at HIV/AIDS specialized care services in São Paulo: Group 1 (G1), n = 1608, 1237 male/371 female, median age 44.3 years old, majority using highly active antiretroviral therapy (HAART); G2, n = 1383, 930 male/453 female, median age of 35.6 years old, majority HAART naïve. Enzyme immunoassays [(EIA) Murex and Gold ELISA] were employed for human T lymphotropic viruses types 1 and 2 screening; Western blotting (WB), INNO-LIA (LIA), real-time PCR pol (qPCR), and nested-PCR-RFLP (tax) were used to confirm infection. Samples were considered human T lymphotropic viruses types 1 and 2 positive when there was reactivity using at least one of the four confirmatory assays. By serological screening, 127/2991 samples were positive or borderline, and human T lymphotropic virus infection was confirmed in 108 samples (three EIA-borderline): 56 human T lymphotropic virus type 1 [G1 (27) + G2 (29)]; 45 human T lymphotropic virus type 2 [G1 (21) + G2 (24)]; one human T lymphotropic virus type 1 + human T lymphotropic virus type 2 (G2); six human T lymphotropic virus [G1 (2) + G2 (4)]. Although there were differences in group characteristics, human T lymphotropic viruses types 1 and 2 prevalence was similar [3.1% (G1) and 4.2% (G2), p = 0.113]. The overall sensitivities of LIA, WB, qPCR, and PCR-RFLP were 97.2%, 82.4%, 68.9%, and 68.4%, respectively, with some differences among groups, likely due to the stage of human T lymphotropic virus infection and/or HAART duration. Indeterminate immunoblotting results were detected in G2, possibly due to the seroconversion period. Negative results in molecular assays could be explained by the use of HAART, the occurrence of defective provirus and/or the low circulating proviral load. In conclusion, when determining the human T lymphotropic virus infection, the findings highlight that there is a need to consider the blood samples with borderline results in screening assays. Of all the tested assays, LIA was the assay of choice for detecting human T lymphotropic virus type 1 and human T lymphotropic virus type 2 in human immunodeficiency virus type 1-infected patients.